Analysis of vacA, cagA, and IS605 Genotypes and Those Determined by PCR Amplification of DNA between Repetitive Sequences of Helicobacter pylori Strains Isolated from Patients with Nonulcer Dyspepsia or Mucosa-Associated Lymphoid Tissue Lymphoma - van Doorn, Nathalie E. M. (American Society for Microbiology, 1999)
The vacA s and m genotypes and the presence of cagA and IS605 were determined in Helicobacter pylori strains from patients with mono- and multiple infections. Surprisingly, these genetic markers were not associated with nonulcer dyspepsia or mucosa-associated lymphoid tissue lymphoma. The presence of cagA correlated with the presence of the vacA s1 allele (P < 0.05), whereas the presence of IS605 was associated with the presence of the s2 allele (P < 0.05).